FRAMING PEMBERITAAN “PEMBONGKARAN PUNGKRUK” PADA SURAT KABAR SUARA MERDEKA - Mahfudlah Fajrie; Ika Suryani Kusuma Dewi (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2016)
This research was conducted to know the objectivity of Suara Merdeka newspaper on the news related to conflict of demolition of karaoke building and culinary business in Pungkruk area Mororejo village, Mlonggo sub-district, Jepara regency. The research method used is qualitative by using Robert framing approach. N. Entman. Sources of data in this study are primary data, data obtained from the Suara Merdeka reporting from 3 August to 16 October 2016 edition, and secondary data in the form of papers on Suara Merdeka and books related to Robert's framing analysis. N. Entman. The results of his research are 1) framing conducted by journalists Suara Merdeka in news texts written tend to use a single point of view in defining the problem. This is done by reporters by giving more space to the Jepara regency statements in written texts than with statements from entrepreneurs Pungkruk and society; The dominant figure in the reporting texts written by journalists is Jepara Pemkab while Pungkruk entrepreneurs are figures who are considered as the cause of the problem, while the community is a supporter of Jepara regency policy; The journalist's report uses two depictions of moral values, positive and negative values. Positive values are often raised against the depiction of District Government actions, whereas negative values are often raised against the description of the actions of the Pungkruk entrepreneur; 2) reporters Suara Merdeka in preaching conflicts related dismantling Pungkruk building is less balanced, because it tends to prioritize the Jepara regency and marginalize the position of entrepreneurs.